The Eschatological Imagination in Literature - Wolfe, Judith (Religion & literature, 2024)
This article examines the role of the eschatological imagination in literature. It begins by arguing that eschatology, far from being abstract or outdated, shapes both individual and collective imagination and desire, orienting lives toward an implied or explicit end. In modernity, traditional religious eschatologies have often been replaced by political, technological, or psychological visions of fulfillment, many of which result in "eschatological antinomies" - the self-defeating pursuit of desire., Literature, Wolfe contends, provides a unique space to live within the tension between longing for resolution and acknowledging the impossibility of full closure. Works by Shakespeare, Eliot, Tolkien, and others embody a dual movement: they draw readers toward a sense of meaning while simultaneously letting go, resisting total narrative containment. This mirrors the Christian eschatological vision - a promise that is glimpsed but not yet realized. Such literature becomes a training ground for hope: not an escapist fantasy, but a way of preparing the heart to live well amid uncertainty. Like the liturgy, these works offer a moment of transformation that sends the reader back into life with both courage and humility.